The Effects of Non-Surgical Periodontitis Therapy on the Clinical Features and Serological Parameters of Patients Suffering from Rheumatoid Arthritis as Well as Chronic Periodontitis - Ding, Nan; Luo, Mei; Wen, Ya-Hui; Li, Rong-Yin; Bao, Qi-Yan (Journal of inflammation research, 2022)
The present study aims to evaluate the effects of basic periodontal disease therapy on the general condition and serum inflammatory indicators of patients with rheumatoid arthritis (RA) combined with chronic periodontitis (CP). Forty patients with RA were enrolled in the study and, based on the results of an oral examination and in line with the 2018 periodontitis diagnostic criteria, they were divided into a group with CP (the RA + CP group) and a group without CP (the RA group). Twenty-nine patients with CP who attended the periodontal department of our hospital were recruited as a group with only CP (the CP group), and 20 volunteers without any systemic or periodontal disease were recruited as a healthy control group (the H group). The periodontal and joint conditions of the subjects in the four groups were recorded; anti-cyclic citrullinated protein antibodies, interleukin 6 (IL-6), C-reactive protein (CRP), the erythrocyte sedimentation rate (ESR), and rheumatoid factor levels, which reflect the severity of the RA, were detected, and the differences between the groups were analyzed. The probing depth (PD), clinical attachment loss, and sulcus bleeding index (SBI), which reflect the severity of the periodontitis, were correlated with the factor levels. The RA + CP and CP groups received therapeutic intervention, and the differences in each indicator before and six weeks after the treatment were compared, and their data were compared with those of patients in the RA group and H groups. Compared with the RA group, the serum expressions of ESR, CRP, and IL-6 were significantly higher in the RA + CP group. There were significant differences in the levels of PD, SBI, IL-6, and CRP in the patients receiving basic periodontal disease therapy before and after the treatment. A relatively large proportion of patients with RA have chronic periodontitis, and the local inflammatory state of CP might exacerbate the systemic inflammatory response in RA. Basic periodontal disease therapy may improve the oral condition of patients with RA and reduce the serum levels of the inflammatory factors.